SAE Technical Paper Series 1992
DOI: 10.4271/921968
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced/Synthetic Vision Systems: Human Factors Research and Implications for Future Systems

Abstract: This paper reviews recent human factors research studies conducted in the Aerospace Human Factors Research Division at NASA Ames Research Center related to the development and usage of Enhanced or Synthetic Vision Systems. Research discussed includes studies of field of view (FOV), representational differences of infrared (IR) imagery, head-up display (HUD) symbology, HUD advanced concept designs, sensor fusion, and sensor/database fusion and evaluation. Implications for the design and usage of Enhanced or Syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…10 Investigators have found that the display clutter and field-of-view issues already mentioned for tunnel-only displays are even more of an issue when combined with synthetic vision, and additional human factors issues such as pilot over-fixation on the symbology are introduced. 11 There have been many more studies in this area of tunnel and synthetic vision situational awareness augmentation, but this brief survey illustrates some of the issues that were also of concern during our work here at Boeing.…”
Section: B Synthetic Vision-based Studiesmentioning
confidence: 96%
“…10 Investigators have found that the display clutter and field-of-view issues already mentioned for tunnel-only displays are even more of an issue when combined with synthetic vision, and additional human factors issues such as pilot over-fixation on the symbology are introduced. 11 There have been many more studies in this area of tunnel and synthetic vision situational awareness augmentation, but this brief survey illustrates some of the issues that were also of concern during our work here at Boeing.…”
Section: B Synthetic Vision-based Studiesmentioning
confidence: 96%
“…Distortion: The polynomials (15) and (16) model the windshield distortion. To display the image generated in the previous step correctly, we apply an inverse distortion on the image.…”
Section: Two-pass Renderingmentioning
confidence: 99%
“…The idea of using HUDs as an Augmented Reality device was originally introduced and explored for avionic applications [15,10,9,21]. Here, pilots are assisted in navigating the plane safely in the air or on the ground by visualizing flight corridors or by highlighting taxiways when the visibility is low.…”
Section: Introductionmentioning
confidence: 99%
“…Background of synthetic vision and human factor issues has been briefed in a panel discussion 6 from the perspective of government, academic, military and industry. D.C. Foyle 7 , et al have reviewed some of the research related to enhance synthetic vision systems. Out-of-the-window viewing in low visibility weather with limited display characteristics, that may result in degradation of the visual cues, is discuss.…”
Section: Synthetic Visionmentioning
confidence: 99%